Characterization and phylogenetic analysis of the complete mitochondrial genome in Xiaoxiang chicken (Gallus gallus domesticus). Issue 1 (2nd January 2020) - Liu, Lili; Ren, Mengya; Yang, Yeqi; Chen, Zhehui
Abstract: Xiaoxiang chicken ( Gallus gallus domesticus ) is one of the native breeds in the Southeastern of Guizhou province, China. The complete mitochondrial genome sequence of Xiaoxiang chicken (small-sized breed chicken) was obtained for the first time. The mitogenome is 16, 784 bp in length, and it contained a D-loop region, two rRNA genes, 13 protein-coding genes, and 22 tRNA genes. A neighbour-joining phylogenetic tree was structured based on the D-loop, which indicated that the Red junglefowl was the direct ancestor of Xiaoxiang chicken, and both were closed to the Silky chicken and Dongan black chicken.